Residual strain investigation of a polycrystalline quartzite rock sample using time-of-flight neutron diffraction - Badmaarag, Altangerel; Sangaa, Deleg; Sikolenko, Vadim V.; Enkhtur, Lkhamsuren (Mongolian Geoscientist, 2023)
In this work, we studied the residual micro lattice strain of an onyx sample, which is a micro- to the cryptocrystalline variety of the mineral quartz SiO2. That the investigation has been carried out using in-situ stress experiments with the time-of-flight neutron diffraction method. The aim of the study is to investigate residual lattice strains and pressure directions in the sample using time-of-flight neutron diffraction, which is a powerful tool for the study of the residual strain behavior in bulk materials, like geological rock samples containing large grains. The residual strain was detected in different sample directions turning the sample in steps of 30° by 180° around the cylindrical z-axis. These experiments have been performed at the time-of-flight neutron strain diffractometer EPSILON, situated on the pulsed neutron source IBR-2M of the Joint Institute for Nuclear Research in Dubna, Russia. The results of this study will provide insights into the compressional and tensional residual strain of the crystallographic lattice planes, and will have implications for our understanding of the tectonic history of this region. These different strains are arranged in the sample by a sinusoidal distribution in radial directions.